Mass media representation of suicide in a high suicide state in India: an epidemiological comparison with suicide deaths in the population. Issue 7 (18th July 2019) - Armstrong, Gregory; Vijayakumar, Lakshmi; Pirkis, Jane; Jayaseelan, Mala; Cherian, Anish; Soerensen, Jane Brandt; Arya, Vikas; Niederkrotenthaler, Thomas
Abstract : Objectives: Suicide rates in India are among the highest in the world, equating to over 200 000 suicides annually. Reports of suicides are a routine feature in major newspapers in India, and reporters may selectively present 'newsworthy' suicide stories. The aim of this paper was to systematically investigate whether mass media reports of suicides reflect the epidemiological data on suicide in a high suicide state in India. Design: We undertook a content analysis study to extract sociodemographic data on suicides reported among nine of the most highly read daily newspapers in the high suicide southern state of Tamil Nadu between June and December 2016. A total of 1258 newspaper articles were retrieved containing reports on 1631 suicides. Two-tailed binomial tests on aggregate frequencies assessed whether the sociodemographic characteristics of suicides in the newspaper articles were different to the population suicide statistics for Tamil Nadu. Results: We identified some statistically significant discrepancies between suicide characteristics in the population and the media. Suicides involving females (p<0.001), those aged under 30 years (p<0.001), separated or widowed males (p<0.001), unmarried females (p<0.001), those using methods with a higher case fatality rate (ie, hanging (p<0.001), jumping off high structures (p<0.001) and coming under vehicles (p<0.001) and those who were students (p<0.001) or working in the agricultural sector (p<0.001) were significantly over-reported relative to their occurrence in the broader population. Suicides involving men (p<0.001), those aged over 30 years and above (p<0.001), those who were married and suicides by poisoning (p<0.001) were significantly under-reported relative to their occurrence in the broader population. Conclusions: The suicide characteristics in the print media were not entirely representative of suicides in the broader Tamil Nadu population, which may lead the general public to develop misunderstandings about suicide in their state. The discrepancies we identified will inform tailored suicide prevention education for media professionals.